PERSONAL DEIXIS AS ADDRESSING SYSTEM TO EXPRESS SOLIDARITY AT CAMPUS COMMUNITY - SriAgung, Winantu Kurnianingtyas (JL3T (Journal of Linguistics, Literature and Language Teaching), 2017)
This research investigates personal deixis that indicate solidarity in campus environment. Students and lecturers conversation transcription were collected and analyzed by the researcher to identify the types of personal pronoun that commonly used to pointer the participants. The result showed that there were three kinds of pronoun used commonly by the participants and those indicate close relationship among others such as first person singular, second person singular, and third person plural. The finding revealed that the second person singular of bro, sist, and jeng are common in pointing speakers’ audience. Eventhough, those become slang language in society. The implication of this research suggested for other types of pronoun to be exist in campus environment and indicate power.